Codificação de fonte - Bonfim, Juliano de Falque [UNESP] (2014)
This work consists of a study about the basic principles of source coding. In this sense we develop the basics of data source, information and entropy, requirements to present the Shannon's Source Coding Theorem as well as the result that provides the parameters and limitations for source coding without loss of information. The Huffman Code is discussed for their theoretical importance and the work is concluded with a description of the Lempel-Ziv Algorithm